2008
DOI: 10.1186/1756-0500-1-62
|View full text |Cite
|
Sign up to set email alerts
|

Are residential and nursing homes adequately screening overseas healthcare workers?

Abstract: Background: There has been significant growth in the number of healthcare workers born outside the UK or recruited to the UK from countries with a high prevalence of TB, Hepatitis and other blood borne infections. Government policy recognises the need for occupational health procedures to facilitate treatment for these individuals and to reduce the risk of transmission of disease to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A survey conducted in 2008 in the South East of England identified that the majority of care homes (largely private sector) did not have OH policies and provided no assessment for TB in HCWs born abroad. 27 The finding that the majority of HCW TB cases in this cluster were employed by the private sector and did not have OH check highlights the importance of ensuring that all healthcare employers have appropriate OH provision for TB assessment. Other UK studies identified, unlike our findings, that the majority of HCWs with TB had pre-employment healthcare checks before their diagnosis with active TB.…”
Section: Discussionmentioning
confidence: 87%
“…A survey conducted in 2008 in the South East of England identified that the majority of care homes (largely private sector) did not have OH policies and provided no assessment for TB in HCWs born abroad. 27 The finding that the majority of HCW TB cases in this cluster were employed by the private sector and did not have OH check highlights the importance of ensuring that all healthcare employers have appropriate OH provision for TB assessment. Other UK studies identified, unlike our findings, that the majority of HCWs with TB had pre-employment healthcare checks before their diagnosis with active TB.…”
Section: Discussionmentioning
confidence: 87%